The use of alternative ingredients in food for tambaqui (Colossoma macropomum): a review (Research, Society and Development, 2022)
The use of non-conventional ingredients is an option to reduce costs in the production of feed for tambaqui (Colossoma macropomum) which is currently the most produced native species in Brazil. Thus, the objective of this study was to evaluate the state of the art of research on the use of alternative ingredients to replace conventional ones in tambaqui feed, identifying the main products of Brazilian biodiversity used, as well as the advantages and disadvantages of including these ingredients in the feed for this species. A narrative review of the literature on the subject was carried out, searching for scientific articles in major databases (Scielo and Scopus), in addition to the Google Scholar tool, available digitally, from 2010 to 2022. The results showed that the use of alternative ingredients in the tambaqui diet to replace conventional ingredients was promising in most of the studies reviewed, except for cupuaçu cake; pineapple, mango, and passion fruit pulp; banana meal, and ginger essential oil, whose inclusion in the diet interfered negatively in the indexes evaluated. Of the alternative ingredients used in the research 93.75% were of plant origin, mainly Amazonian fruits. Only juveniles were used in the research and only 31.25% of the papers determined the digestibility coefficients. Thus, further research should be directed towards finding a better combination of the alternative ingredients and the best balance of nutrients, especially for fish above 125 g.